PENGGUNAAN AUGMENTED REALITY (AR) PADA MATERI PENGUKURAN TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI KELAS IV SEKOLAH DASAR - Sevia Palupi Dwi Ningrum; Alif Luthvi Azizah; Jody Setya Hermawan; Muhammad Nurwahidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study is the low level of motivation among pupils in learning mathematics. Pupils still regard mathematics as a difficult subject and therefore lack enthusiasm for participating in lessons. This study aims to determine the effect of the use of learning media on the motivation of Year 4 pupils to learn mathematics. This study employs a quantitative approach in the form of a quasi-experimental design. The population in this study comprises all Year 4 pupils at SDIT Annawawi Metro. The research sample consists of Year 4 Class Roudhoh as the experimental class, comprising 26 pupils, and Year 4 Class Nabawi as the control class, comprising 21 pupils. The sampling technique employed non-probability sampling using the purposive sampling method. Data collection was carried out through the distribution of questionnaires and observation, and was subsequently analysed using simple linear regression. The hypothesis of this study was that there is an effect of the use of Augmented Reality (AR) media on the mathematics learning motivation of Year 4 pupils at SDIT Annawawi Metro, based on the results of the simple linear regression test; therefore, the alternative hypothesis (Hₐ) was accepted. Based on the analysis results, an Adjusted R-Square value of 0.484 or 48% was obtained, meaning that the variable of Augmented Reality (AR) media implementation was able to explain 48% of the variation in learning motivation, whilst 52% was influenced by other variables outside the scope of the study